Assessment of the Use of Liquefied Petroleum Gas (LPG) as a Cooking Energy Source Among Households in the Wa Municipality, Ghana. - Nibenang, M. (University of Ghana, 2023)
The persistent use of traditional cooking fuels in many developing countries, including Ghana, poses significant health and environmental concerns. More than half of households in Ghana rely on biomass as their primary cooking fuel. Although the government of Ghana launched the National LPG Promotion Campaign to increase access to cleaner cooking fuels, adoption rates have been slow, particularly in the Wa municipality where households continue to practice fuel stacking. Therefore, the study sought to assess the dynamics in the adoption and use of LPG as an energy source for cooking among households within the Municipality. A total of 220 households within three selected communities in the study area were sampled to take part in the study survey. Furthermore, key informant interviews were conducted with relevant stakeholders to gain an in-depth understanding of the quantitative data analysis. The findings reveal that most LPG users in the study area adopted the fuel as a secondary cooking fuel. Additionally, fuel stacking was widespread with households using both traditional and modern fuels simultaneously, indicating a non-linear transition in fuel use. A chi-square test of association and a binary logistic regression model further showed a significant relationship between the use of LPG and some selected sociodemographic characteristics of households within the study area.
MA. Development Studies
Keywords: traditional cooking fuels; Ghana; LPG